An experimental study on the performance of guided bubble pump with multiple tubes. (5th August 2016) - Lin, Falong; Liu, Daoping; Jiang, Danqing; Yang, Liang; Zhao, Rongxiang
Highlights: The cone-mouthed multiple lift-tube bubble pump has a good ability in lifting working fluid. The ideal flow regime for the experiments is basically slug flow. Pumping effectiveness could be as high as 13.89% with additional risers. Increasing the number of riser will not result in lifting capacity and efficiency in direct proportion. Abstract: Bubble pump's capacity has been largely restricted because of low efficiency, therefore a cone-mouthed multiple lift-tube bubble pump was designed to evaluate its performance in this paper. Experiments are conducted under atmospheric pressure with tubes of three different diameters (8 mm, 10 mm and 12 mm), in regard to three kinds of submergence ratios (0.3, 0.4, 0.5), and the tubes are tested in groups of different numbers, ie, groups of 1, 2, 3, 4 and 5 tubes. Water is filled into tubes as working fluid, and the heating power ranges from 100 W to 2000 W. Based on the theoretical model of two-phase flow, we compared the experimental data, it is evidenced that the multiple tubes bubble pump performance improves when the submergence ratio increases, and so does riser number. In addition, flow patterns are observed and recorded at three representative heating powers, it is discovered that the experimental values are in reasonable agreement with the theoretical values only in the region of slug-flow. Furthermore slug flow pattern can be seen clearly in the region where the heating power ranges from 100 W to 2000 W, consequently the ideal flow regime for the experiments is basically slug flow.